The Application of Discretion in Criminal Offenses Related To Narcotics in The Regional Police Force (Polda) of Bali - Oktaviadi, I Gusti Ngurah; Wiratny, Ni Ketut; Damanik, Siti Nurmawan (Asian Journal of Social and Humanities, 2025)
As guardians of public order, police officers are often faced with situations that require them to take actions outside of standard procedures to ensure public safety and order, especially in drug-related cases, where police officers may disregard the necessary requirements when conducting initial actions. How the Application and Obstacles of Discretion in Drug-Related Criminal Offenses in the Bali Regional Police (Polda Bali) The theories used as analytical tools are the Rule of Law Theory, the Legal Theory, Authority Theory, and Law Enforcement Theory. The type of research is normative research using a legal approach and a conceptual approach. The legal sources used are primary, secondary, and tertiary legal materials. Legal materials were collected through inventory. The analysis of the materials was conducted using descriptive, interpretive, and argumentative techniques. The exercise of discretion in narcotics-related criminal cases by the Bali Regional Police; the police have arrested suspects in narcotics-related criminal cases without prior arrest warrants, based on reasonable belief and consideration, acting swiftly and decisively to immediately apprehend the suspects. The challenges faced by the Bali Regional Police Narcotics Investigation Unit in conducting investigations into drug abuse offenders include insufficient funding , lack of community participation, insufficient cooperation with the community, and the persistence of a culture of bribery.